Integrated Solution for As(III) Contamination in Water Based on Crystalline Porous Organic Salts - Xiaoxia Yang; Qi Guo; Xingman Liu; Jing‐xin Ma (Advanced Science, 2024)
Abstract A stable crystalline organic porous salt (CPOSs‐NXU‐1) with 1D apertures has been assembled by the solvothermal method, which shows high‐sensitivity “turn‐on” fluorescence detection and large‐capacity adsorption of As(III) ions in water. The detection limits, saturated adsorption capacity, and removal rate of CPOSs‐NXU‐1 for As(III) ions in an aqueous solution can reach 74.34 nm (5.57 ppb), 451.01 mg g−1, and 99.6%, respectively, at pH = 7 and room temperature. With the aid of XPS, IR, Raman, and DFT theoretical calculations, it is determined that CPOSs‐NXU‐1 adsorbed As(III) ions in the form of H2AsO3− and H3AsO3 through hydrogen bonding between the host and guest. The mechanism for fluorescence sensitization of As(III) ions to CPOSs‐NXU‐1 is mainly to increase the energy level difference between the ground state and excited state investigated by UV–vis absorption spectra, UV–vis diffuse reflectance spectra, and theoretical calculations. By constructing fluorescent CPOSs, an integrated solution has been achieved to treating As(III) contamination in the water that is equipped with detection and removal. These results blaze a promising path for addressing trivalent arsenic contamination in water efficiently, rapidly, and economically.